Preliminary studies on additive manufacturing of over 95% dense 3Y zirconia parts via digital imaging projection - do Amaral, Letícia Bueno; Paschoa, Jorge Luis Faneco; Magalhães, Daniel Varela; Foschini, Cesar Renato [UNESP]; Suchicital, Carlos T. A.; Fortulan, Carlos Alberto (Springer Nature, 2020)
Additive manufacturing of ceramic materials has been evolving greatly. Yet, in the last 5 years, techniques based on lithography began to emerge with an emphasis on obtaining dense parts. The present work deals with the experimental study of additive manufacturing of 3Y zirconia via digital imaging projection. For this purpose, a commercial light projection system was set up with a mechanical spreader (blade) of paste layers on an x–y–z built platform. Formulations developed for a ceramic powder loaded with a photo-polymerizable resin and solvents were printed. After printing, the specimens were fired for solvents and resin removal, sintered and characterized. Digital projection (without filter) provided UV and visible light enough to polymerize the resin in layers of up to 50 µm thickness. Low-porosity zirconia bodies (3.4%) were obtained using mixtures with ceramic powder/resin concentration up to 50 vol%. Solvent removal under air pressure (3 bar) in an autoclave at 50 °C resulted in low lamination effects and avoided bubbles evolution. Three-point flexural test in non-machined sintered bars reached an average stress of 337 MPa. The results are very promising and demonstrate that the additive manufacturing of ceramic parts based on a digital imaging projection process is a viable alternative.
Keywords: 3D printing; Additive manufacturing of ceramics; Photo-polymerization in vat